2020
DOI: 10.3389/fpsyg.2020.552305
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Personality, Political Attitudes and Socio-Demographic Characteristics in Explaining Individual Differences in Fear of Coronavirus: A Comparison Over Time and Across Countries

Abstract: Since the emergence of the SARS-CoV-2 pandemic in December 2019 about 500,000 people died within the first 6 months. The virus itself, as well as the related political decisions, intensified an increasing feeling of fear in billions of people worldwide. However, while some people remained unperturbed, others experienced panic over the current situation. In order to investigate individual differences in the perceptions, emotions and behaviors in response to the Coronavirus pandemic, an online survey was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
1
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 28 publications
5
43
1
2
Order By: Relevance
“…From a range of nearly forty functions, those related to regulating negative and boosting positive affect increased the most in importance during the COVID-19 lockdown, such as enjoyment, relaxation, comfort, distraction, and a reduction of stress and anxiety. All of these functions directly target the negative wellbeing effects of the COVID-19 pandemic (Dagnino et al, 2020;Dawel et al, 2020;Franceschini et al, 2020;Groarke et al, 2020;Hur, Smith, DeYoung, Anderson, Kuang, Kim, Tillman, Kuhn, Fox, & Shackman, 2020;Lenzo et al, 2020;Lippold et al, 2020;Parlapani et al, 2020;Rajkumar, 2020;Rodríguez-Rey et al, 2020;Rossi et al, 2020). Ultimately, these findings extend our knowledge about music usage to a global public health crisis, beyond previous studies that have identified the importance of music as a tool for emotional regulation in everyday life (Juslin & Sloboda, 2010;Saarikallio, 2011;Thoma, Ryf, Mohiyeddini, Ehlert, & Nater, 2012;Randall, Rickard, & Vella-Brodrick, 2014;Groarke & Hogan, 2016).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…From a range of nearly forty functions, those related to regulating negative and boosting positive affect increased the most in importance during the COVID-19 lockdown, such as enjoyment, relaxation, comfort, distraction, and a reduction of stress and anxiety. All of these functions directly target the negative wellbeing effects of the COVID-19 pandemic (Dagnino et al, 2020;Dawel et al, 2020;Franceschini et al, 2020;Groarke et al, 2020;Hur, Smith, DeYoung, Anderson, Kuang, Kim, Tillman, Kuhn, Fox, & Shackman, 2020;Lenzo et al, 2020;Lippold et al, 2020;Parlapani et al, 2020;Rajkumar, 2020;Rodríguez-Rey et al, 2020;Rossi et al, 2020). Ultimately, these findings extend our knowledge about music usage to a global public health crisis, beyond previous studies that have identified the importance of music as a tool for emotional regulation in everyday life (Juslin & Sloboda, 2010;Saarikallio, 2011;Thoma, Ryf, Mohiyeddini, Ehlert, & Nater, 2012;Randall, Rickard, & Vella-Brodrick, 2014;Groarke & Hogan, 2016).…”
Section: Discussionsupporting
confidence: 53%
“…Such is the case during the COVID-19 pandemic. In addition to fear of the virus (Lippold et al, 2020) and elevated stress levels due to physical-distancing measures (Best, Law, Roach, & Wilbiks, 2020), many people faced (and continue to face) reduced income or unemployment, the need to combine working from home with childcare duties, uncertainty about the future, and social isolation. Evidence is accumulating for severe negative mental health impacts, such as increased levels of anxiety, depression, stress, loneliness, and impaired sleep quality (Dagnino et al, 2020;Dawel et al, 2020;Franceschini et al, 2020;Groarke et al, 2020;Hur, Smith, DeYoung, Anderson, Kuang, Kim, Tillman, Kuhn, Fox, & Shackman, 2020;Lenzo et al, 2020;Lippold et al, 2020;Parlapani et al, 2020;Rajkumar, 2020;Rodríguez-Rey et al, 2020;Rossi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, as the pandemic escalated, fear of being infected increased significantly. According to a recent study by a German psychology research group, the strongest predictors of fear were personality variables, as well as education, sex and being an at-risk person [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…From a psychological viewpoint, research has largely been aimed at assessing the impact on persons’ mental, emotional and behavioral health from the periods of confinement that a large part of the population has been subjected to ( Lippold et al, 2020 ; Spalleta et al, 2020 ). The effects of confinement on mental health have been analyzed by a number of authors ( Taylor, 2019a , b , c ; Sokolowska et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%